ETHNOSCIENCE IN BIOLOGY LEARNING ON REPRODUCTIVE SYSTEM MATERIALS - Tuti Marjan Fuadi; Irdalisa (Postgraduate, University of Mataram, 2024)
This research aims to examine ethnoscience in biology learning on the reproductive system. The research method is a quantitative approach with a quasi-experimental type of research with pre-test and post-test applied and grouped into three categories of high, medium and low. The research was carried out at the Darussalam State Madrasah Aliyah Aceh Besar Regency, Aceh. The research results show that there has been an increase in students' understanding and abilities which can be seen from the increase in post-test results. Ethnoscience on the reproductive system can be studied from a series of cultural practices from the process of pregnancy to birth. Students can connect scientific science with real science in their environment. Students can also appreciate and preserve local community knowledge related to reproductive system material. So it can be concluded that ethnoscience learning can enrich students' experiences by introducing local wisdom and cultural diversity that exists in society.